Functional Outcomes to Surgical Treatment of the Distal Humerus Intra-Articular Fractures in Adults - Yigman, Abdulkadir; Tuncer, Nejat; Erdil, Mehmet; Bilsel, Kerem; BİLSEL, İSMAIL KEREM; Elmadag, Mehmet; ELMADAĞ, NUH MEHMET; Sen, Cengiz (My University, 2013)
Aim: Displaced and intraarticular humerus distal fractures require surgical treatment. In this study we evaluated to functional results of the surgical treatment of distal humerus intraarticular fractures in adults. Additionally, we evaluated the factors affecting surgical outcomes. Material and Method: Between 2005 to 2010, 22 elbows of 21 patients who were operated for distal humerus intraarticular fractures were evaluated retrospectively. 11(52.4%) patient were male and 10(47.6%) were female, mean age 46.2 (range 17 to 71). Fractures were classified as type B3 for 10, type Cl for 6 and type C2 for 6 subjects according to AO classifications. We performed paralel double locking plate for 9(41%), perpendicular double plate for 2(9%), K wires and screw combination for 7(32%), and single plate for 4(18%) patients. Functional assesment were performed with the MEPS and q-DASH scoring systems. Results: Mean follow-up was 30.4(5-68) months. Fracture healing was observed in all of the patients. Mean elbow flexion of 117 (90145) degrees and extension loss of 24.3 (0-60) were noted. 10 (47.6%) patients were excellent, 6 (28.6%) were goad, 3 (14.3%) were fair and 2(9.5%) were poor according to MEPS. Mean q-DASH scores were 15 (0-69.8) in 21 patients. Good results were obtained in fractures treated with stable fixation, in early performed surgeries, and in early started rehabilitation. Discussion: Treatment of distal humerus intraarticular fractures with anatomical reduction, stable osteosynthesis, and early rehabilitation are very important in obtaining successful outcomes. Additionally, age and fracture type are important factors to conclude good results..